Guiding principles for identification, evaluation and conservation of Vitis vinifera subsp. sylvestris - Zdunic, G.; Maul, E.; Eiras Dias, J.E.J.; Muñoz Organero, G.; Carka, F.; Maletic, E.; Savvides, S.; Jahnke, G.G.; Nagy, Z.A.; Nikolic, D.; Ivanisevic, D.; Beleski, K.; et al. (Institute for Grapevine Breeding (germany), 2017)
Conservation of grapevine genetic resources is an important and long lasting task. Here, partners of the InWiGrape Activity of the European Cooperative Programme for Plant Genetic Resources have proposed a set of descriptors that will assist in identification, conservation and study of genetic resources of Vitis vinifera L. subsp. sylvestris. A distribution map of Vitis vinifera L. subsp. sylvestris populations in Europe was produced, with on-line access through the European Vitis Database. The several different aspects of conservation of Vitis vinifera L. subsp. sylvestris including bibliographical references, identification in the wild, in situ and ex situ conservation have been discussed. The descriptors and the map will assist different stakeholders, working on biodiversity and ecosystems in more effective conservation of wild grapevine genetic resources.